American Accounting Association. (The Accounting Review, 1991)
Abstract The article presents information on the American Accounting Associations committees for the year 1990-1991. It includes advisory groups of Executive Committee; Council; Regional Vice Presidents; Section Officers; Accounting Accreditation Committee; Accounting Education Advisory Committee; Bylaws Committee; Awards Evaluation Committee; Association Staffing Evaluation Committee and others.